(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Kummoo W, Teampanpong J, Paansri P, Suksavate W, Utsa P, Duengkae P, Prompat S. 2020. Impact of highway on vertebrate roadkill in Nam Nao National Park, Thailand. Biodiversitas 21: 5540-5550. Roads lead to biodiversity loss, primarily through wildlife collisions. This phenomenon is widespread, despite limited attention in Thailand. To reduce road mortality, the roadkilled species and their distributions along the road become a significant component for designing management strategies. We surveyed vertebrate mortality covering 44 kilometers of Highway 12, passing through Nam Nao Nation Park in Phetchabun Province of Thailand for 34 replicates between August 2018 and July 2019. We recorded 1,389 carcasses of 578 amphibians, 540 reptiles, 190 mammals and 81 birds. The rate of wildlife-vehicle collisions (WVCs) was 1.089 ± 0.823 carcasses-km-1day-1, comprised mostly of amphibians. The distribution pattern of WVCs was arranged in spatial clusters. Five wildlife collision hotspots for four taxa groups were identified. Overall, the WVC presence was positively associated with vegetation types but negatively associated with distance to the forest edge, the presence of road barriers and the number of road lane. Concurrently, the numbers of roadkill incidents were positively associated with amphibians more than other vertebrate groups, the night time and number of daily vehicles. Our results suggest that WVC rates on HW12 vary among taxonomic groups, temporal scales and environmental factors. It highlights key hotspots where mitigation strategies should be implemented for biodiversity conservation.